Taxonomic notes on Neoperla (Plecoptera: Perlidae) from Sichuan Province of China with the description of two new species - Li, Weihai; Wang, Ying; Wang, Rongfeng (Zootaxa, 2017)
Species of the perlid genus Neoperla from Sichuan Province, China are reviewed. Two new species are described, Neoperla caii Li & Wang, sp. nov. and N. emeishana Li & Wang, sp. nov. The new species are compared with related congeners. Available types of several known Neoperla species from Sichuan Province were studied and complementary descriptions or brief taxonomic comments are presented for N. bilineata Wu & Claassen, N. chui Wu & Claassen, N. microtumida Wu & Claassen, N. quadrata Wu & Claassen and N. truncata Wu.